"Embrace the Yogic Path to Holistic Health and Wellness" (International Journal of Food and Nutritional Sciences, 2022)
In today's rapidly advancing world, where science and technology have significantly improved our quality of life, the unintended consequences of such progress are becoming evident in the form of pollution, restlessness, and a lack of genuine happiness, especially among the younger generation. This article, , delves into the profound practice of Yoga as a means to address these modern challenges.